Non-Indigenous Species (NIS) Know No Geopolitical Borders—An Update of NIS in the Aegean Sea - Argyro Zenetos; Alper Doğan; Ahmet Kerem Bakir; Georgios Chatzigeorgiou; Maria Corsini-Foka; Ertan Dağli; Athanasios Evangelopoulos; Engin Meriç; Maria Stoumboudi; Ergun Taşkin; Mehmet Baki Yokeş; Marika Galanidi (Diversity)
In this work, combined efforts by Greek and Turkish scientists produced an updated validated NIS inventory of the Aegean ecoregion, covering 120 years of records up to August 2024. Of the 342 NIS currently present in the Aegean Sea, the majority (281 species) have invaded the South Aegean, followed by the North Aegean (128 species out of 206 NIS). A total of 73 species were added to the list, while 56 were removed. Overall, unaided spread of Lessepsian immigrants from the Levantine Sea and shipping are equally responsible for NIS reported at the regional level. An increase in publications addressing NIS matches the upward trend of NIS since the mid-1990s, which continues to the present day. While unaided introductions of Lessepsian species and/or direct introductions via the Suez Canal peaked in the South Aegean during 2000–2005, they peaked in 2012–2017 in the North Aegean—a decade later. The opposite pattern was observed in ship-transferred NIS. The spatial distribution of introduction hotspots largely reflects the following phenomena/processes: unaided introduction is witnessed initially in the southeastern Aegean Sea; monitoring efforts are concentrated in vulnerable and at-risk areas; and research efforts relate to the spatial allocation of institutions and marine experts working on marine NIS along the Aegean coasts.